Enhanced band-edge photoluminescence from ZnO-passivated ZnO nanoflowers by atomic layer deposition - Ai, Zhi Wei (Springer, 2013)
The ZnO nanoflowers were synthesized by reactive vapor deposition. A secondary nucleation in the stalk/leaves interface was suggested. The photoluminescence revealed that there were many oxygen vacancies in the nanoflowers. To tune the optical properties of ZnO nanoflowers, ZnO thin films with varying thicknesses were coated on the nanoflowers by atomic layer deposition, which can distinctly improve the band-edge photoluminescence properties.